Mortality of tanners. - Pippard, E C (1985)
The mortality of 833 male tannery workers known to have been employed in the industry in 1939 and who were followed up to the end of 1982 was studied. A total of 573 men had been employed in making leather tanned by vegetable extracts for soles and heels, and 260 men had used chrome tanning to make leather for the upper parts of shoes. No significant excesses of deaths were found for any of the common sites of cancer in either group of workers. One death from nasal cancer (0.21 expected) was reported among the men who worked with sole and heel leather.